Multi-events development. Workshop developing athletes between 8 and 12 years of age - Robertson, S.; Munro, M. (IFAC, 2013)
At the International Festival of Athletics Coaching from 25.-27. Oktober 2013 in Glasgow/Scotland the autors present their thoughts about multi-events development and the development of athletes between 8 and 12 years of age. The aim of the authors ist to create, resource and deliver a comprehensive and effective coach development system for athletics in Scotland based on key stages of athlete progression. They present their "age and stage development model", key focus areas for coach/athletes, athlete development principles, recommendations for structuring sessions etc.